(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The article investigates the criteria for teaching the discipline of Folk Pedagogy through modular technologies in contemporary higher pedagogical education. The scientific problem is determined by a methodological contradiction: on the one hand, folk pedagogy is a culturally dense field that transmits historical memory, moral norms, social experience, family-communal upbringing practices, oral creativity, customs and national values; on the other hand, modern higher education increasingly requires measurable learning outcomes, flexible curricula, independent learning trajectories, transparent assessment and competence-based didactic design. The purpose of the study is to substantiate a system of criteria that allows the teacher to transform folk pedagogy from a descriptive course on traditions into a modular, research-oriented and practice-related discipline. The study relies on comparative-pedagogical analysis, document analysis, didactic modelling and expert generalisation. The main result is a criterion matrix including cultural-authenticity, goal-competence, modular-structural, methodological-activity, reflective-axiological, diagnostic-assessment, digital-resource and implementation-sustainability criteria. The proposed criteria can be used for syllabus design, module passport development, lesson planning, assessment rubrics, independent study tasks and monitoring of student achievement. The article argues that modular technology does not mechanise folk pedagogy; rather, when pedagogically grounded, it protects the integrity of cultural content while making learning outcomes visible, assessable and transferable to future professional practice. The novelty of the work lies in interpreting folk pedagogy as a modular competence system in which national educational heritage is connected with contemporary didactics, learner autonomy and professional teacher training.